Predicting critical power in elite cyclists: questioning the validity of the 3-Minute all-out test - Bartram, J. C.; Thewlis, D.; Martin, D. T.; Norton, K. I. (International Journal of Sports Physiology and Performance, 2017)
Purpose: New applications of the critical-power concept, such as the modeling of intermittent-work capabilities, are exciting prospects for elite cycling. However, accurate calculation of the required parameters is traditionally time invasive and somewhat impractical. An alternative single-test protocol (3-min all-out) has recently been proposed, but validation in an elite population is lacking. The traditional approach for parameter establishment, but with fewer tests, could also prove an acceptable compromise.